PORPE (PREDICT, ORGANIZE, REHEARSE, PRACTISE AND EVALUATE) AS AN EFFECTIVE METHOD FOR TEACHING ENGLISH AT STUDENTS OF VOCATIONAL HIGH SCHOOL - Puspa Dewi (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2017)
ABSTRACT: This paper deals at proposing PORPE (Predict, Rehearse, Practise, and Evaluate) as an effective and interesting method to teach English for vocational high school. PORPE method can be used in any content area course that uses the essay exam to measure learning or any test format that encourages higher level softhinking such as synthesis, application, and evaluation. The five steps of PORPE operationalize the cognitive and metacognitive processes that effective readers engage in to understand and subsequently learn content area material. The students will get benefits from the implementation of PORPE method in teaching English for vocational high school. Keywords: POPRE (Predict, Rehearse, Practise, and Evaluate) method, effective, teaching, vocational high school ABSTRAK: Tujuan dari artikel ini yaitu memaparkan metode PORPE (Predict, Rehearse, Practise, and Evaluate) yang efektif dan menarik dalam pembelajaran bahasa Inggris untuk siswa SMK. Metode PORPE dapat digunakan untuk pembelajaran semua materi yang didalamnya menggunakan tes esai untuk merangsang tingkat berpikir yang lebih tinggi meliputi sintesis, aplikasi, dan evaluasi. Kelima tahapan dari penerapan metode PORPE melibatkan proses berpikir secara kognitif dan metakognitif yang memungkinkan pembaca aktif lebih termotivasi untuk memahami dan selanjutnya mempelajari isi dari meteri pembelajaran. Para siswa dapat memperoleh banyak manfaat dari pembelajaran yang mengaplikasikan metode PORPE. Kata kunci: metode PORPE (Predict, Rehearse, Practise, and Evaluate), efektif, pembelajaran, SMK